Enrichment musical workshop of the attention program for students with early behavior giftedness (PAPCS) - Koga, Fabiana Oliveira [UNESP]; Moriel Chacon, Miguel Claudio [UNESP] (Univ Federal Goias, 2015)
This article aims to present the process of musical evaluation and one of the enrichment experiences conducted between 2013 and 2014 with 17 kids, from the Attention Program for Students with Early Behavior Giftedness (PAPCS) of the Faculty of Philosophy and Science of Sao Paulo State University - UNESP, Campus Marilia/SP. Based on theorists like Edwin Gordon and Violeta H. de Gainza, this study counted on the use of music evaluations instruments: Primary Measures of Music Audition (PMMA), Intermediate Measures of Music Audition (IMMA) (GORDON, 1986) and the guiding sheet of music conduct (FOOCM) (GAINZA, 1988). Likewise, based on the Enrichment Model for Gifted, from Joseph S. Renzulli, and on the theorists of Music Education this paper presents the Music enrichment process that was conducted after the evaluation, as a continuity of a process that aimed to maximize and turn increasingly accessible the contact of these kids evaluated with music.
Keywords: Musical giftedness; Evaluation; Musical enrichment workshop